2011
DOI: 10.1111/j.1445-2197.2010.05347.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative fine needle cytology and imaging facilitates the management of submandibular salivary gland lesions

Abstract: This series demonstrates histological outcomes in patients specific to the submandibular salivary gland. The malignancy rate was low compared to current published literature. The transcervical surgical approach to submandibular gland pathology is a safe and effective method with minimal morbidity when performed by experienced surgeons. No single investigative modality can be solely aligned with diagnosing a specific lesion of the submandibular gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Despite its wide acceptance as a diagnostic tool with low rates of complication and patient morbidity, interpretation of salivary gland FNA specimens remains one of the most challenging areas within cytopathology. Factors contributing to this difficulty include overlapping morphological features between benign and malignant entities, the vast heterogeneity of tumour nodules, lesional cell resemblance to normal salivary gland elements, metaplastic or cystic changes mimicking neoplasms, the need to evaluate capsular invasion (which cannot be done on FNA) and the presence of focal atypia—all of which can preclude precise categorisation of salivary gland lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its wide acceptance as a diagnostic tool with low rates of complication and patient morbidity, interpretation of salivary gland FNA specimens remains one of the most challenging areas within cytopathology. Factors contributing to this difficulty include overlapping morphological features between benign and malignant entities, the vast heterogeneity of tumour nodules, lesional cell resemblance to normal salivary gland elements, metaplastic or cystic changes mimicking neoplasms, the need to evaluate capsular invasion (which cannot be done on FNA) and the presence of focal atypia—all of which can preclude precise categorisation of salivary gland lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is frequently used together with FNA, and is an effective guidance tool to facilitate the aspiration procedures (6). The first published study discussing the combination of multiple strategies to obtain higher diagnostic accuracy for salivary gland lesions, was carried out by Taylor et al in 2011 (5). The authors concluded that sonography, sialography and FNA are effective diagnostic tools guiding the decision for surgical intervention, with CT, MRI and core biopsies declared as useful adjuncts in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, approximately 10% to 15% of all salivary gland tumors occur in the submandibular glands, and approximately 50% of these are malignant . Although less commonly performed, FNA is also the diagnostic method of choice for diagnosing submandibular gland lesions The literature review shows an overall diagnostic accuracy higher than 80% with a sensitivity of 71.4% and a specificity of 94.4% …”
Section: Introductionmentioning
confidence: 99%